Prevalence of mental health disorders and their association with chronic physical diseases in Kuwait - Al-Ozairi, Abdullah; Irshad, Mohammad; Alsarraf, Fatmah; Raina, Sagarika; Alsaraf, Husain; Al Ozairi, Ebaa (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to evaluate the prevalence of mental health disorders and their associations with chronic physical diseases in secondary healthcare settings in Kuwait.MethodsThis retrospective cross-sectional study analyzed data collected from electronic health records of psychiatric care units in secondary healthcare hospitals in Kuwait. Mental health disorders were diagnosed by professionals and documented using the International Classification of Diseases, 10th Revision (ICD-10). We collected both mental and physical health data, along with basic demographic information. Logistic regression models adjusted for age, sex, drug abuse, and developmental disorders were used to examine associations. Results are reported as adjusted odds ratios (AOR) with 95% confidence intervals (CI).ResultsA total of 11921 patient records from psychiatric units in secondary care hospitals were analyzed. Among these patients, 41.1% (n= 4902) had a chronic mental health disorder, with depression being the most common (33.7%, n= 4023). Comorbid chronic mental health disorders and chronic physical diseases were observed in 19.5% (n= 2319) of patients. Patients with chronic physical diseases were 1.8 times more likely to have a chronic mental health disorder compared to those without chronic diseases (AOR=1.8, 95% CI: 1.6–2.0, p< 0.001). Depression was significantly associated with cancer (AOR, 2.9; 95%CI, 2.4–3.6), diabetes (AOR, 2.0; 95%CI, 1.7–2.3), renal disease (AOR, 1.8; 95%CI, 1.5–2.1), hypertension (AOR, 1.7; 95%CI, 1.4–2.0), neurological disease (AOR, 1.6; 95%CI, 1.4–1.8), cardiovascular disease (AOR, 1.5; 95%CI, 1.3–1.8), and respiratory disease (AOR, 1.2; 95%CI, 1.0–1.5). Somatic symptom disorder was significantly associated with neurological disease (AOR, 1.6; 95% CI, 1.3–2.0).ConclusionsThis study revealed a substantial burden of mental health disorders, with depression showing significant associations with multiple chronic physical diseases. However, causal inferences cannot be drawn from this cross-sectional design. These findings are hypothesis-generating and highlight the need for further research on systematic mental health monitoring in secondary care populations.